The Effect of Digital Finance Adoption, the Role of Microfinance Institutions and Financial Literacy on Microenterprise Technological Innovation with Transaction Costs as a Moderator - Aulia Sofia Meilinda; Embun Suryani; I Nyoman Nugraha AP (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of digital finance adoption, the role of microfinance institutions, and financial literacy on technological innovation in micro businesses with transaction costs as a moderating variable. The study used a quantitative approach with purposive accidental sampling method on 150 respondents of micro business actors in the western southeast Nusa Tenggara region and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that digital finance adoption and financial literacy have a significant positive effect on micro business technological innovation, while the role of microfinance institutions showed a positive but insignificant effect. Moderation tests revealed that transaction costs have no effect on the adoption of digital finance, microfinance institutions and financial literacy on technological innovation